A Basic Laboratory Medicine Library. Issue 7 (30th January 2016) - Hytjan, Kay; Brondos, Gregory A.
Abstract : This article describes a basic or "core" library for a medical laboratory. Members of all the councils of the American Society of Clinical Pathologists (ASCP) were asked to submit the names of three texts, three journals, and three miscellaneous educational publications that they considered to be basic in their respective fields. The results were tabulated for each ASCP council with the exception of the councils on Graduate and Undergraduate Education and Special Topics. Annotation of all textbooks was provided by the authors, publishers, and editors.